Transplantation of fecal filtrate to neonatal pigs reduces post-weaning diarrhea: A pilot study - Larsen, Christina; Andersen, Amanda B.; Sato, Helena; Brunse, Anders; Thymann, Thomas (Frontiers in Veterinary Science, 2023)
Post-weaning diarrhea (PWD) remains a major source of mortality and morbidity in swine production. Transplantation of bacteria-free filtrate of feces (fecal filtrate transplant, FFT) has shown gut protective effects in neonatal pigs, and early postnatal establishment of the gut microbiome is suggested to determine later stability and robustness of the gut. We, therefore, hypothesized that early postnatal transplantation of bacteria-free feces would have a protective effect against PWD. Using fecal filtrates derived from healthy lactating sows, we compared oral administration of fecal filtrate transplantation (FFT, n=20) and saline (CON, n=18) in newborn piglets. We assessed growth, diarrhea prevalence, blood parameters, organ measurements, morphology, and gut brush border enzymes and analyzed luminal bacterial composition using 16S rRNA gene amplicon sequencing. The two groups showed similar average daily gain (ADG) during the suckling period, whereas in the post-weaning period, a negative ADG was observed in both groups. While diarrhea was largely absent in both groups before weaning, there was a lower diarrhea prevalence on days 27 (p=2.07*10-9), 28 (p=0.04), and 35 (p=0.04) in the FFT group relative to CON. At weaning on day 27, the FFT group had higher numbers of red blood cells, monocytes, and lymphocytes, while on day 35, i.e. one week after weaning, the two groups were similar regarding hematology. The biochemical profile was largely similar between FFT and CON on days 27 and 35, except for a higher level of alanine aminotransferase and a lower level of Mg in the FFT group. Likewise, organ weights relative to body weight were largely similar on day 35, albeit with a lower stomach weight and more colon content in FFT relative to CON. Gut mucosal percentage and mucosal enzyme activity were similar between the two groups on days 27 and 35. Gut bacterial composition was slightly different on day 35 but not on day 27. In conclusion, early postnatal administration of FFT, showed positive clinical effects in post-weaning pigs, albeit with subtle effects on the gut mucosa and microbiome. Prophylactic treatment with FFT may offer a means to reduce morbidity, yet larger studies are required to document effect size.